Rhodium-catalyzed oxidative C–H allylation of benzamides with 1,3-dienes by allyl-to-allyl 1,4-Rh(III) migration - Korkis, Stamatis E.; Burns, David J.; Lam, Hon Wai (American Chemical Society, 2016)
The Rh(III)-catalyzed oxidative C–H allylation of N-acetylbenzamides with 1,3-dienes is described. The presence of allylic hydrogens cis- to the less substituted alkene of the 1,3-diene is important for the success of these reactions. With the assistance of reactions using deuterated 1,3-dienes, a proposed mechanism is provided. The key step is postulated to be the first reported examples of allyl-to-allyl 1,4-Rh(III) migration.